Geometric Function Theory In Several Complex Variables, Proceedings Of A Satellite Conference To The Int'l Congress Of Mathematicians In Beijing 2002. - FitzGerald, Carl H. (World Scientific, 2004)
The papers contained in this book address problems in one and several complex variables. The main theme is the extension of geometric function theory methods and theorems to several complex variables. The papers present various results on the growth of mappings in various classes as well as observations about the boundary behavior of mappings, via developing and using some semi group methods.